Gain Saturation and Pulse Solutions for a CO2-HE T.E.A. Laser - Tricker, Terence (My University, 1973)
The saturation behaviour of various gain models for the CO2-HE T.E.A. laser was investigated. The corresponding laser pulse shapes for an oscillating cavity were generated by computer and compared to experimentally observed output pulses. Good agreement is obtained for low gain using a simple two-level model but at high gain, vibrational coupling between levels must be included.
Title: Gain Saturation and Pulse Solutions for a CO2-HE T.E.A. Laser, Author: Terence Tricker, Location Thode